Formulation and Evaluation of Polymeric Micells Loaded With Antidiabetic Drug - Dipali Bawankar; Dr. Sandeep Atram; Vrushabh Mandwe; Aakash Bhonde; Ashutosh Puri (Asian Journal of Pharmaceutical Research and Development, 2025)
Polymeric micelles have gained significant attention as nanocarriers for antidiabetic drug delivery, addressing challenges such as poor solubility and rapid clearance associated with conventional therapies.This research focuses on the formulation and evaluation of polymeric micelles encapsulating an antidiabetic agent, aiming to enhance its bioavailability and therapeutic efficacy.Micelles were prepared using amphiphilic block copolymers by thin film hydration method, with parameters such as polymer concentration, drug loading, and micelle size optimized to achieve desired characteristics.The formulations were characterized for particle size, zeta potential, drug entrapment efficiency, drug loading and in vitro release profile.The results revealed that this method is reproducible, more feasible and led to the entrapment of drug with an expected sustained release. The nanoparticle precipitated was with particle size of 192.7 nm, zeta potential of −21.72 mV. The entrapment efficiency noted was 36.12. In vitro release was about 11.33 % release in 6 h. When the regression coefficient values were compared, it was observed that ‘R2’ values of first order was maximum i.e. 0.9806 hence indicating drug release from formulation was found to follow first order release kinetics. Antidiabetic drug-loaded polymeric micells may be a good choice for the improvement of solubility, bioavailability and reduction in toxicity. This research underscores the efficacy of polymeric micelles as a viable strategy for the controlled delivery of antidiabetic drugs, offering a promising approach to improve patient compliance and therapeutic outcomes.